Early onset epilepsy and sudden unexpected death in epilepsy with cardiac arrhythmia in mice carrying the early infantile epileptic encephalopathy 47 gain‐of‐function FHF1(FGF12) missense mutation. (13th May 2021) - Velíšková, Jana; Marra, Christopher; Liu, Yue; Shekhar, Akshay; Park, David S.; Iatckova, Vasilisa; Xie, Ying; Fishman, Glenn I.; Velíšek, Libor; Goldfarb, Mitchell
Summary: Objective: Fibroblast growth factor homologous factors (FHFs) are brain and cardiac sodium channel‐binding proteins that modulate channel density and inactivation gating. A recurrent de novo gain‐of‐function missense mutation in the FHF1(FGF12) gene (p.Arg52His) is associated with early infantile epileptic encephalopathy 47 (EIEE47; Online Mendelian Inheritance in Man database 617166). To determine whether the FHF1 missense mutation is sufficient to cause EIEE and to establish an animal model for EIEE47, we sought to engineer this mutation into mice. Methods: The Arg52His mutation was introduced into fertilized eggs by CRISPR (clustered regularly interspaced short palindromic repeats) editing to generate Fhf1 R52H /F+ mice. Spontaneous epileptiform events in Fhf1 R52H /+ mice were assessed by cortical electroencephalography (EEG) and video monitoring. Basal heart rhythm and seizure‐induced arrhythmia were recorded by electrocardiography. Modulation of cardiac sodium channel inactivation by FHF1BR52H protein was assayed by voltage‐clamp recordings of FHF‐deficient mouse cardiomyocytes infected with adenoviruses expressing wild‐type FHF1B or FHF1BR52H protein. Results: All Fhf1 R52H /+ mice experienced seizure or seizurelike episodes with lethal ending between 12 and 26 days of age. EEG recordings in 19–20‐day‐old mice confirmed sudden unexpected death in epilepsy (SUDEP) as severe tonic seizures immediately preceding loss of brain activity and death. Within 2–53 s after lethal seizure onset, heart rate abruptly declined from 572 ± 16 bpm to 108 ± 15 bpm, suggesting a parasympathetic surge accompanying seizures that may have contributed to SUDEP. Although ectopic overexpression of FHF1BR52H in cardiomyocytes induced a 15‐mV depolarizing shift in voltage of steady‐state sodium channel inactivation and slowed the rate of channel inactivation, heart rhythm was normal in Fhf1 R52H /+ mice prior to seizure. Significance: The Fhf1 missense mutation p.Arg52His induces epileptic encephalopathy with full penetrance in mice. Both Fhf1 (p.Arg52His) and Scn8a (p.Asn1768Asp) missense mutations enhance sodium channel Nav 1.6 currents and induce SUDEP with bradycardia in mice, suggesting an FHF1/Nav 1.6 functional axis underlying altered brain sodium channel gating in epileptic encephalopathy.